Woolly Stories: An Art-Based Narrative Approach to Place Attachment (Engaged Scholar Journal: Community-Engaged Research, Teaching, and Learning, 2019)
When people join an institution, no assurance of positive social connection exists. The mechanisms of psychological attachment to institutions are not well understood. However, place attachment is a predictor of individual well-being and, when correlated with life satisfaction and neighborhood ties, can enhance civic engagement and social trust. Research suggests that narratives can be a symbolic mechanism of place attachment. Thus, to increase place attachment in the parent population at a small elementary school,  various art-based narrative activities were carried out as part of the OurSchoolOurStories project. Creating a storied blanket was one activity. Seven women needle-felted nine squares with the theme of representing some aspect of what the school meant to them. In a circle, they shared many stories including where they came from, how they came to be at the school, and their experiences at the school. Through these artistic narratives, participants were able to share much about their place identities, which allowed for social connection, and a sense of integration within the group.